Influence Of Pentagon Fraud On Fraudulent Financial Reporting: Ministry Of Timor-Leste - Caetano Carceres Correia; Siti Munawaroh (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine how pentagon fraud can affect financial reporting fraud in Timor-Leste ministries. This study was conducted in 8 Timor-Leste ministries with a sample of 88. The analysis technique used in this study was simple regression using SPSS. The results of the study indicate that with a significance level of 5% (percent), pentagon fraud has a positive effect on financial reporting fraud. This indicates that the higher the pentagon fraud, the higher the financial reporting fraud in Timor-Leste ministries. The results of the study indicate that pentagon fraud has an influence on financial reporting fraud. Based on the results of interviews with respondents in Timor-Leste ministries, many people still use opportunities to commit financial reporting fraud, this is due to the lack of supervision from auditors to identify several opportunities that will be used by irresponsible people to commit financial reporting fraud